2020
DOI: 10.1093/jamia/ocaa130
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a digital chatbot to screen health system employees during the COVID-19 pandemic

Abstract: SUMMARY The screening of healthcare workers for COVID-19 symptoms and exposures prior to every clinical shift is important for preventing nosocomial spread of infection but creates a major logistical challenge. To make the screening process simple and efficient, UCSF Health designed and implemented a digital chatbot-based workflow. Within one week of forming a team, we conducted a product development sprint and deployed the digital screening process. In the first two months of use, over 270,000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
102
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(111 citation statements)
references
References 4 publications
0
102
1
8
Order By: Relevance
“…Additionally, our review showed that health chatbots were used in multiple domains. The most prevalent domains were preventive care and risk communication (n=3) ( 3 , 9 , 12 ), public health surveillance by health officials (n=2) ( 2 , 10 ), Telehealth (n=2) ( 1 , 11 ), workplace health and safety (n=1) ( 13 ), and care of the elderly (n=1) ( 14 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, our review showed that health chatbots were used in multiple domains. The most prevalent domains were preventive care and risk communication (n=3) ( 3 , 9 , 12 ), public health surveillance by health officials (n=2) ( 2 , 10 ), Telehealth (n=2) ( 1 , 11 ), workplace health and safety (n=1) ( 13 ), and care of the elderly (n=1) ( 14 ).…”
Section: Resultsmentioning
confidence: 99%
“…Amazon released Alexa VA features to help users setup routines during staying at home and providing tips, information, and guidance about COVID-19 16 . Frameworks for COVID-19 screening with chatbots have been proposed and implemented at healthcare institutions 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Symptoma, a symptom-to-disease digital health assistant using AI, has been shown to be highly accurate when screening for COVID-19 [ 65 ]. Similarly, chatbots have been used to rapidly screen health care workers for COVID-19, facilitating staff movements and minimizing nosocomial transmission [ 66 ]. By extension, AI-based chatbots can provide a platform for patients with non–COVID-19 conditions to receive medical care at a time when clinical resources are limited.…”
Section: Discussionmentioning
confidence: 99%